Effect of biomechanical factors on energy cost during running at varying inclines - Seki, K.; Sugimoto, K.; Kyröläinen, H.; Enomoto, Y. (ISBS Proceedings Archive (Michigan), 2017)
This study aimed to investigate the characteristics of muscular activity of a support leg that affected energy cost at different inclinations of a treadmill while running. Eleven male Japanese distance runners ran on a treadmill at 13.5 km/h for 3 min at five different inclinations 6%, 3%, 0%, +3%, and +6%. Running kinematics, electromyography (EMG), expired gases, and blood lactate levels were measured. The following results were obtained: 1) the energy cost and integrated EMG (iEMG) of the vastus lateralis (VL) muscle increased with increasing inclination, and 2) iEMG of the VL and gluteus maximus (GM) muscles positively correlated with the vertical displacement of the body`s center of mass and with a maximal angle of the thigh during the contact phase. Thus, the muscular activities of VL and GM might increase the energy cost while running at an inclination